How HR Strategies Shape PT Pelabuhan Indonesia 1’s Future - Ningsih; Sugianto; Nurbaiti (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
This paper examines the human resource management (HRM) strategies employed by PT Pelabuhan Indonesia 1 (Persero) to enhance employee performance. Using qualitative descriptive analysis and the SWOT framework, the study evaluates key HR practices in recruitment, placement, development, and performance evaluation. Findings reveal significant strengths, such as a skilled workforce, advanced performance management systems, and educational rewards, which enable the organization to capitalize on opportunities like market expansion and technological innovations. However, challenges persist, including inconsistent recruitment policies, limited interdepartmental collaboration, and economic fluctuations. Strategic insights highlight the importance of leveraging internal strengths and external opportunities to mitigate threats and address weaknesses. The study concludes that PT Pelabuhan Indonesia 1 (Persero)’s HRM initiatives align with its growth-oriented objectives, providing a robust foundation for sustained success in a competitive industry. Recommendations include fostering teamwork, refining recruitment processes, and investing in technological advancements to maintain a competitive edge.